Institutional reform paths - Clemens Buchen (Economics & Politics, 2023)
This paper develops a dynamic population game in which agents play a simple anonymous-exchange game of cooperating or defecting. Agents switch to the strategy with a higher expected payoff. Reformers can affect the payoff structure of the stage game to maximize the number of cooperators in the population by either enacting legal reform (institutional quality of contract law) or focusing on the macro outlook of the economy. Based on the theoretical model, the paper predicts which types the reformer should enact first and under which conditions reform will not be successful.
Keywords: 330; macroeconomic political economy; microfoundations of political economy; property rights; reform/stabilization; social choice